CARTOGRAPHY AND TOURISM IN RURAL AREA IN SOUTHERN BRAZIL - Walkowski, Marinês da Conceição; Rebollar, Paola; Raitz, Crisley Silveira; Loch, Carlos (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
Tourism is an important economic activity in many countries. There are different types of interest, among which we highlight tourism in rural areas. This type tourist meets the need to integrate environmental conservation activities in a multifunctional agriculture for rural development sustainable. The rural southern Brazil has the potential for this activity as a function of significant scenic beauty, rich culture and local knowledge related to the agrarian structure based on small family farms whose economic viability requires the variation of activities so pluriativa.